Kalalat-an sa Banwa sang Culasi a descriptive history of disaster and disaster management of the local government in the Municiaplity of Culasi (1940-2013) - Alon, Glaiza Ann C.
This research paper is a descriptive history of disasters and disaster management in the municipality of Culasi from 1940 to 2013. The municipality of Culasi is located in the Philippine archipelago which is prone to disastes. Over the years, the municipality had experienced various kinds of disastrous natural hazards and disasters, including tropical cyclones, flood, earthquakes, and landslides. Tropical storms and cyclones are the most frequent natural hazard, while flooding is a natural disaster which has caused the most and widest damage. Earthquakes are the most destructive to human lives and are usually exacerbated by landslides, although the latter is the least experienced natural hazard in the municipality. In order to lessen and/or avoid the destructive impacts of these disasters, the local government of the municipality has implemented disaster management in areas of prevention, and mitigation, preparedness, response, rehabilitation and recovery.